2000
DOI: 10.1046/j.1529-8817.2000.98251.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF NUTRIENT AVAILABILITY ON THE BIOCHEMICAL AND ELEMENTAL STOICHIOMETRY IN THE FRESHWATER DIATOM STEPHANODISCUS MINUTULUS (BACILLARIOPHYCEAE)*

Abstract: The objective of this study was to examine the differences in the biochemical and elemental stoichiometry of a freshwater centric diatom, Stephanodiscus minutulus (Grun.), under various nutrient regimes. Stephanodiscus minutulus was grown at μ or 22% of μ under limitation by silicon, nitrogen, or phosphorus. Cell sizes for nutrient-limited cultures were significantly smaller than the non-limited cell sizes, with N-limited cells being significantly smaller than all other treatments. Compared with the nutrient-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
122
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(140 citation statements)
references
References 61 publications
13
122
2
3
Order By: Relevance
“…Each spectrum is a mean of 10 replicate spectra, each collected over a randomly selected 10 Â 10 mm area of continuous cellular monolayer. The increased synthesis of carbohydrates and lipids seen in this study reflect those seen under P-deficiency in other algae, including the green alga Ankistrodesmus (Kilham et al, 1997) and the diatom Stephanodiscus (Lynn et al, 2000). Changes in carbon allocation during exponential phase suggest that increases in cellular storage products, particularly carbohydrate, occurred when the cells were still undergoing division.…”
Section: Discussionsupporting
confidence: 58%
“…Each spectrum is a mean of 10 replicate spectra, each collected over a randomly selected 10 Â 10 mm area of continuous cellular monolayer. The increased synthesis of carbohydrates and lipids seen in this study reflect those seen under P-deficiency in other algae, including the green alga Ankistrodesmus (Kilham et al, 1997) and the diatom Stephanodiscus (Lynn et al, 2000). Changes in carbon allocation during exponential phase suggest that increases in cellular storage products, particularly carbohydrate, occurred when the cells were still undergoing division.…”
Section: Discussionsupporting
confidence: 58%
“…The fatty acids content as well as the ratio between unsaturated and saturated fatty acids is an important parameter for determination of algae value. SFAs were found to increase by increasing the iron amount in Nannochloropsis oculata 20 . In Dunaliella tertiolecta and Stephanodiscus minutulus, changes of the SFA's values were directly related to changes in the amount of nitrogen 24 .In the present study, SFAs showed significantly positive correlationship with manganese and iron first of all, then sodium which were sufficiently present in Trenkenshu medium (Table 3 and Figure 5).…”
Section: Discussionmentioning
confidence: 93%
“…The quantity and quality of fatty acids content as well as the entire biochemical composition varies in response to environmental conditions 8,20,24,25,38,39 . Particularly, under unfavorable environmental or stress conditions for growth, such as salinity, temperature, pH, and nutrient levels, many algae alter their lipid biosynthetic pathways towards the formation and accumulation of neutral lipids to control intracellular stress 13,40 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations